Principles and Applications of Data Science - Liu, Chuan-Ming (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Data science is an emerging multidisciplinary field which lies at the intersection of computer science, statistics, and mathematics, with different applications and related to data mining, deep learning, and big data. This Special Issue on "Principles and Applications of Data Science" focuses on the latest developments in the theories, techniques, and applications of data science. The topics include data cleansing, data mining, machine learning, deep learning, and the applications of medical and healthcare, as well as social media.